(untitled) (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2023)
The aim of the present study was to evaluate the hypoglycemic activity of asafoetida and essential oil of asafoetida (EOA) in ovariectomised (OVX) diabetic rats. Twenty-four female rats were divided into four groups consisting of 6 rats in each group. OVX Control, OVX diabetic, OVX diabetic and asafoetida (25 mg/kg), OVX diabetic and EOA 25 μL/kg. Fasting Blood glucose, lipid profiles and liver indices were measured, and liver and kidney histopathology was investigated. Urine volume, urea, creatinine, and microalbumin were measured. The neuropathic damage was assessed by the hot plate method. The results showed that only in the asafoetida group the blood sugar, ALT and AST levels decreased significantly. Consumption of food, water, and body weight also decreased in the asafoetida grouponly. Also, regarding histology, relative improvement was observed in kidney and liver tissue in the asafoetida group. A significant decrease in urine volume and improvement in creatinine, urea and microalbumin concentrations, as well as improvement in hot plate test response time, were observed in both treatment groups. It can be concluded that asafoetida is effective in treating diabetes, but its essential oil has no effective activity on diabetes mellitus.